A remarkable new species of Coeliccia from the Tuyen Lam Lake area, Lam Dong, southern Vietnam (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A. (Zootaxa, 2016)
Coeliccia suoitia sp. nov. (holotype ♂, from Suoi Tia, Tuyen Lam Lake, Da Lat, Lam Dong Province, Vietnam, deposited in RMNH) is described from males from southern Vietnam. It is a distinctive species that possess highly unusual characters in the thorax and anal appendages that make its ultimate generic placement questionable. Relationships between Coeliccia Kirby, Asthenocnemis Lieftinck and Indocnemis Laidlaw, and within Coeliccia, are briefly discussed.